Improving the Quality of Medical Handover Through the ISBAR³ Technique in Children’s Health Ireland at Temple Street - Ryan, Alicia; Pereira, Doireann (Trinity Student Medical Journal, 2024)
Background: Medical handover is considered an important aspect of patient care to provide safe and quality care to patients. As the medical community moves away from 24-hour shifts, there is a greater need for a standardised handover to be implemented. Medical handover techniques are currently being criticised for their lack of structure, often leading to errors in patient care. Improvement in medical handover is crucial, as transfer in care can be associated with hospital mortality. We aimed to integrate interactive prompts and brief teaching sessions on the ISBAR³ technique to improve the quality and standardisation of medical handover. Methods: Plan-Do-Study-Act (PDSA) methodology was employed. Four cycles, each of a 3-day duration, were completed over a 4-week study period. Data collection and introduction of implementation measures were completed from Monday to Friday to increase staff awareness. The methodology of each cycle was developed from the outcomes of previous cycles and discussions with key stakeholders. Results: The baseline data of this project revealed inconsistent and unreliable use of some aspects of the ISBAR³ handover tool. The second cycle displayed an overall improvement in the engagement of ISBAR³. The areas of Identify, Situation, Background, and Assessment averaged 100% utilisation across all days of phase 2. Outcomes of the third cycle revealed continuous engagement with ISBAR³, inferring the beneficial use of multi-media prompts. Outcomes of the final cycle, focused on clinical handover adherence and standardise access to computer software, showed significant improvement in all areas of the medical handover. Conclusion: This PDSA–based quality improvement project demonstrates the speed at which a high-quality intervention can be rolled out in a high-pressure clinical environment. The 4-cycle PDSA model had a positive impact on the process measures of clinical handover in a tertiary paediatric centre.